Attenuation of acute kidney injury in a murine model of neonatal Escherichia coli sepsis - Esther M. Speer; Atilade A. Adedeji; Joyce Lin; Alexandra Khorasanchi; Asma Rasheed; Maya Bhat; Kelly Mackenzie; Randolph Hennigar; Kimberly J. Reidy; Robert P. Woroniecki (Frontiers in Cellular and Infection Microbiology)
IntroductionSepsis is a risk factor for acute kidney injury (AKI) in neonates, for which no effective treatment exists. The phosphodiesterase inhibitor pentoxifylline (PTX) has demonstrated renal protection from ischemia and inflammation in adult rodents. We hypothesized that addition of PTX to antibiotics may attenuate immune and histological AKI in a murine neonatal sepsis model.MethodsPostnatal (PN) day 1 C57BL/6J mice were injected with E. coli K1 strain at 105 colony forming units per gram weight or saline control. After 1.5 hours, septic pups randomly received saline, gentamicin or cefotaxime, with/without PTX. 5.5h after sepsis initiation, kidneys and blood were harvested for measurements of biomarkers of inflammation and kidney injury. Renal sections from PN7 mice were used for histology and immunofluorescence. Linear mixed effect models were employed to fit the outcomes including interaction between treatment group and sex.ResultsSeptic mice demonstrated robust expression of pro-inflammatory cytokines, chemokines and biomarkers of tubular injury in renal tissue, which were attenuated in response to combined PTX and antibiotics (gentamicin or cefotaxime): chemokines (p<0.001), plasma (p<0.01) and tissue IL-6 (p<0.05), plasma TNF (p<0.001), NGAL (p<0.01), CXCL10 (p<0.01), osteopontin (p<0.05), and VEGF (p<0.05), with a trend for KIM-1 (tissue concentration: p=0.21, fluorescence area: p=0.12). Interactions between treatment and sex were present for several cytokines and kidney injury biomarkers. Immunofluorescence findings for the tubular injury markers (NGAL and KIM-1) were consistent with biomarker expression in tissue lysates.ConclusionNeonatal E. coli sepsis leads to increased expression of renal tissue inflammation and injury biomarkers consistent with AKI, which may be attenuated with PTX combined with antibiotic treatment.